2013
DOI: 10.1089/ten.tea.2012.0249
|View full text |Cite
|
Sign up to set email alerts
|

Novel Methodology Based on Biomimetic Superhydrophobic Substrates to Immobilize Cells and Proteins in Hydrogel Spheres for Applications in Bone Regeneration

Abstract: Cell-based therapies for regenerative medicine have been characterized by the low retention and integration of injected cells into host structures. Cell immobilization in hydrogels for target cell delivery has been developed to circumvent this issue. In this work mesenchymal stem cells isolated from Wistar rats bone marrow (rMSCs) were immobilized in alginate beads fabricated using an innovative approach involving the gellification of the liquid precursor droplets onto biomimetic superhydrophobic surfaces with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Cells exhibited good viability and osteogenic capability. Moreover, in vivo tests showed that these particles could stimulate bone regeneration in cranial defects [246]. More sophisticated layered particles could be obtained by the sequential deposition of hydrogel precursors over previously hardened particles allowing the distribution of cells or drugs in compartments with a radial arrangement [247].…”
Section: Superhydrophobic Surfacesmentioning
confidence: 99%
“…Cells exhibited good viability and osteogenic capability. Moreover, in vivo tests showed that these particles could stimulate bone regeneration in cranial defects [246]. More sophisticated layered particles could be obtained by the sequential deposition of hydrogel precursors over previously hardened particles allowing the distribution of cells or drugs in compartments with a radial arrangement [247].…”
Section: Superhydrophobic Surfacesmentioning
confidence: 99%
“…[ 123 ] Briefl y, pre-particle solutions are dispensed in a patterned mould and then they are solidifi ed by appropriated procedures (e.g., light exposure, temperature, lyophilization, among others) acquiring the shape of the pre-established patterns. As observed for the superhydrophobic technology used to produce spherical particles encapsulating drugs or cells [ 46,[124][125][126][127][128][129][130] the incorporation of drugs (for example) inside such artifi cial erythrocyte-like particles is relatively simple: just mix the bioactive compounds with the material before printing/crosslinking. Biomimetic hydrogel particles of 2-hydroxyethyl acrylate (HEA) cross-linked with PEG diacrylate (PEGDA) exhibited a negative surface charge and mechanical properties similar to those of erythrocytes.…”
Section: Reviewmentioning
confidence: 99%
“…Color images available online at www.liebertpub.com/tec or reactive granuloma formation. 31 Carrageenans biocompatibility has been questioned in the literature. 32,33 Carrageenan is used to induce paw edema in the rat and mouse and induces IL-8 production through distinct Bcl10 pathway in normal human colonic epithelial cells.…”
Section: General Analysis Of Biomaterials' Inflammatory Responsementioning
confidence: 99%